DEVELOPMENT, MANUFACTURING AND TESTING RMS DATA ACQUISITION INSTRUMENT USING ATMEGA32 - HARTANTO (NIM : 13106070); Pembimbing : Dr. Ir. Zainal Abidin, FENDY
There are several machinery condition monitoring methods, one of which is vibration measurement. This method is conducted using vibration sensors dan data acquisisition instrument. This method is widely used in industries, such as UPT Kamojang. Vibration measurement in UPT Kamojang is conducted using vibration velocity sensors and an online data acquisition instrument. The instrument was made in Dynamics Laboratory of PAU-ITB based on Wibisono [1] research. The instrument is then developed by Kusuma [2]. However, the instrument still has some limitations such as it sometimes failed to record vibration level data and itÃ‚Â’s data acquisition mode is still semiautomatic. This research aims to develop online data acquisition instrument capable of overcoming those limitations. The development of the online data acquisition instrument consists of hardware and software developments. The hardware development involves design and manufacturing circuits in PCB. The software development involves development of data acquisition program, data recording and downloading program, and automatic-dataacquisition-mode program. Having done the development, the instrument is tested to determine its performance. The tests consist of linearity, consistency and reliability simulation test using signal generator, and vibration level measurement test using a prototype of balancing machine. The linearity tests show that the data acquisition instrument is fully successful in saving 720 data and has maximum nonlinearity of 2.70%. In addition, the vibration measurement test shows that the maximum error of the instrument is 3,83%. Thus, it can be concluded that the developed data acquisition device has successfully overcome those limitation.